2010
DOI: 10.1007/s10126-010-9257-3
|View full text |Cite
|
Sign up to set email alerts
|

Aspartic Cathepsin D Endopeptidase Contributes to Extracellular Digestion in Clawed Lobsters Homarus americanus and Homarus gammarus

Abstract: Acid digestive proteinases were studied in the gastric fluids of two species of clawed lobster (Homarus americanus and Homarus gammarus). An active protein was identified in both species as aspartic proteinase by specific inhibition with pepstatin A. It was confirmed as cathepsin D by mass mapping, N-terminal, and full-length cDNA sequencing. Both lobster species transcribed two cathepsin D mRNAs: cathepsin D1 and cathepsin D2. Cathepsin D1 mRNA was detected only in the midgut gland, suggesting its function as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
22
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 71 publications
3
22
0
Order By: Relevance
“…We determined that cathepsin D1 expression occurs in the midgut tissue but not in muscle or gonads, while cathepsin D2 appears to be stably expressed at low levels in all three. In this proteomic study, we identified 9 peptides from cathepsin D1 but no peptides from cathepsin D2 which supports our previous hypothesis that cathepsin D2 functions in the endo-lysosomal pathway and not in gastric digestion of food (Rojo et al 2010a). Three peptides corresponding to a S28 family serine peptidase were identified in the gastric juice (GenBank: EX487603.1).…”
Section: Proteomic Analysis Of Gastric Juicesupporting
confidence: 86%
See 3 more Smart Citations
“…We determined that cathepsin D1 expression occurs in the midgut tissue but not in muscle or gonads, while cathepsin D2 appears to be stably expressed at low levels in all three. In this proteomic study, we identified 9 peptides from cathepsin D1 but no peptides from cathepsin D2 which supports our previous hypothesis that cathepsin D2 functions in the endo-lysosomal pathway and not in gastric digestion of food (Rojo et al 2010a). Three peptides corresponding to a S28 family serine peptidase were identified in the gastric juice (GenBank: EX487603.1).…”
Section: Proteomic Analysis Of Gastric Juicesupporting
confidence: 86%
“…This enzyme has been isolated previously, and the pH and temperature for optimum activity has been determined (Rojo et al 2013). This enzyme can readily degrade hemoglobin (Rojo et al 2010a;Rojo et al 2013) and its substrate specificity profile is similar to cathepsin D isolated from the gut European hard tick, Ixodes ricinus (Sojka et al 2012). Both of these enzymes cleave between a pair of hydrophobic residues, particularly when phenylalanine is on the amino-terminal side of the scissile bond.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Additionally, the aspartic endopeptidase, cathepsin D, was found in the gastric fluid of the clawed lobsters Homarus gammarus and H. americanus and was identified as a fully operational extracellular digestive enzyme at the acid pH of gastric fluid (Navarrete del Rojo et al, 2010a). The presence of cathepsin D in the gastric fluid seems unusual as this enzyme is known and well characterized as typical lysosomal and, thus, intracellular endopeptidase.…”
Section: Introductionmentioning
confidence: 99%